Performance of dairy production, reproduction and longevity in Holstein and its crosses with Cebu - Hernández, Arelis; Ponce de León, Raquel (Cuban Journal of Agricultural Science, 2018)
The records of Mambí de Cuba dairy cows (3/4 Holstein 1/4 Cebu), Siboney de Cuba (5/8 Holstein 3/8 Cebu) and Holstein, from three herds were used to determine the effect of the genetic group (GG) and various non-genetic factors, for milk production traits (131 658 lactations of 63 066 cows), reproduction (117 794 reproductive events of 36 331 cows), longevity (18 741 cows) and milk production per life (56 536 cows). The traits of cumulative milk production up to 305 days (M305), duration of lactation (DL), age at first service (A first service), parturition-first service interval (PSI), parturition-gestation interval (PGI), parturition interval (PI),productive life (PL), number of parturition per life (PN) and milk production per life (MPLife) were studied. A mixed linear model was applied, with the use of the SAS MIXED procedure. This model included the fixed effects of the genetics, herd, lactation number, year, parturition time, genetic group interactions x lactation number, genetic group x parturition year and genetic group x parturition time. As random, the cow nested in the herd and the errors were included. For the A first S, PL, PN and MPLife traits, the model did not include the lactation number or its interaction. The fixed effects were significant, except for the parturition time and its interaction with the genetic group in the reproductive and longevity traits. It is concluded that the Mambí de Cuba showed better milk production accumulated during life and high longevity. Key words: dairy cattle, environmental effect, genetic groups